Features of communication in Norwegian parent–child play interactions. Issue 3 (June 2022) - Røe-Indregård, Hanne; Rowe, Meredith L.; Rydland, Veslemøy; Zambrana, Imac M.
Communication is best understood as occurring along three dimensions: interactional, conceptual, and linguistic. However, few studies have examined early parent–child communication along all three dimensions simultaneously. This study examines these three dimensions of communication in Norwegian parent–child interactions during play. Thirty-nine 2-year-old children participated in dyadic interactions with their fathers ( N  = 30) and mothers ( N  = 38). Of these 39 children, 29 engaged in separate interactions with both parents. Father–child and mother–child responsive communication, levels of abstract talk, and language complexity and diversity were examined and compared. Overall, the features of communication were very similar between father–child and mother–child interactions, and there were some noteworthy associations between the features of father–child and mother–child communication within families and dyads. We discuss these findings in reference to the three dimensions and in relation to the specific activity and cultural setting of the study.